Patterns and Development in the English Clause System : A Corpus-Based Grammatical Overview - Green, Clarence (Springer Singapore : Imprint: Springer, 2017)
This book examines in detail the forms and functions of clause combination in English. Using a corpus linguistics methodology, it describes how the English clause system currently behaves, how it has developed over the history of the language, and how the features and properties of English clause combination have important theoretical and empirical significance. Adopting the cognitive-functional Adaptive Approach to grammar, it offers a series of interconnected studies that investigate how English clause combination interacts with the properties of coherence and cohesion in discourse across historical time, as well in contemporary language use. This work contributes to the ever-increasing common ground between corpus linguistics and cognitive-functional linguistics, producing new paths for interdisciplinary research.
Keywords: Linguistics.; Historical linguistics.; Syntax.; Corpora (Linguistics).; elektronické knihy; electronic books